Fatty acid‐binding protein 5 limits the generation of Foxp3+ regulatory T cells through regulating plasmacytoid dendritic cell function in the tumor microenvironment. Issue 1 (20th September 2021) - Kobayashi, Shuhei; Wannakul, Tunyanat; Sekino, Kaname; Takahashi, Yu; Kagawa, Yoshiteru; Miyazaki, Hirofumi; Umaru, Banlanjo Abdulaziz; Yang, Shuhan; Yamamoto, Yui; Owada, Yuji
Abstract: Plasmacytoid dendritic cells (pDCs) promote viral elimination by producing large amounts of Type I interferon. Recent studies have shown that pDCs regulate the pathogenesis of diverse inflammatory diseases, such as cancer. Fatty acid‐binding protein 5 (FABP5) is a cellular chaperone of long‐chain fatty acids that induce biological responses. Although the effects of FABP‐mediated lipid metabolism are well studied in various immune cells, its role in pDCs remains unclear. This study, which compares wild‐type and Fabp5 −/− mice, provides the first evidence that FABP5‐mediated lipid metabolism regulates the commitment of pDCs to inflammatory vs tolerogenic gene expression patterns in the tumor microenvironment and in response to toll‐like receptor stimulation. Additionally, we demonstrated that FABP5 deficiency in pDCs affects the surrounding cellular environment, and that FABP5 expression in pDCs supports the appropriate generation of regulatory T cells (Tregs). Collectively, our findings reveal that pDC FABP5 acts as an important regulator of tumor immunity by controlling lipid metabolism. Abstract : What's new? Regulatory T cells (Tregs) obstruct antitumour immunity, promoting tumour microenvironment formation. Although plasmacytoid DCs (pDCs) are pivotal Treg inducers, the effects of FABP5‐mediated lipid homeostasis in pDCs on Tregs remain unclear. This study suggests that FABP5‐mediated lipid metabolism regulates the commitment of pDCs to inflammatory versus tolerogenic gene expression patterns in the tumour microenvironment. Furthermore, FABP5 deficiency in mice attenuated tumour progression and decreased the tumour microenvironment Treg population. Loss of FABP5 from pDCs also impaired Treg induction. The findings suggest that pDC FABP5 acts as an important regulator of tumour immunity by controlling lipid metabolism.